Expansão rápida da maxila assistida cirurgicamente, em dois e três segmentos: análise por elementos finitos - Koga, Alexandre Fukuzo [UNIFESP] (2016)
Introduction: The treatment of transverse maxillary deficiency in adults may need surgically assisted rapid maxillary expansion (SARME). There are various osteotomy techniques of several authors who propose the best technique to solve this deficiency. One way to compare these techniques is the use of the Finite Element Method (FEM). Objective: To compare the pattern of distribution of displacement and stress in SARME in osteotomy techniques in two and three segments using the FEM. Methods: two models of the maxilla were constructed, based on CT scans of adults with expander Hyrax, from the CTI database - Renato Archer (Campinas), through the design of computer-assisted method (BioCAD). A model underwent SARME with subtotal osteotomy Le Fort I complete and step in zygomaticomaxillary pillar and pterygomaxillary disjunction in 2 segments (2S). The other model underwent osteotomy in 3 segments (3S) with vertical osteotomy between the lateral incisors and canines, continuing horizontal and parallel to the sutures toward the rear edge of the hard palate, was also carried out horizontal osteotomy with step on the anterior wall of the maxillary sinus, the piriform aperture to pterygomaxillary suture then held bilateral pterygomaxillary disjunction. Both used a simulation of the expander Hyrax submitted to an expansion of 0.5mm. After the expansion and calculation by FE program (Nei Nastran - Noran Engineering Inc), the displacements were calculated (mm) in the X (transverse), Y (anteroposterior), Z (vertical) and principal maximum and minimum tensions (MPa) in nine anatomical points of the jaw: 1- Tip of buccal cusp of the 1st premolar; 2- Cement enamel junction of the 1st premolar; 3- Edge Wala in the region of the 1st premolar; 4-Projection of the long axis of the 1 st premolar at the time of Le Fort I osteotomy; 5- A b s t r a c t | 102 Cusp tip mesio buccal molar 1; 6- Cement enamel junction of the 1 st molar; 7- Edge Wala in 1 st molar region; 8-projection of the long axis of the 1 st molar at the time of Le Fort I osteotomy; 9 Pterygomaxillary junction. Results: The model of the osteotomy in three segments (3S) had higher displacement of teeth and bones in the three planes of space in relation to the model of two segments (2S). The maximum principal stress (traction) and the minimal principal streess (compression) the teeth were similar in both models. The tensile stress and compression in the bone structures were higher in the 2S model. Conclusions: The 3S osteotomy presents higher transverse displacement in the bone and teeth, lower vertical slope and larger transverse displacement in anterior region. The tension is lower in the 3S osteotomy in the anterior region.